An efficient high speed, high frequency domino-logic based circuit - Zare, Mahdi; Manouchehrpour, Hossein; Esmaeilkhah, Ahmad (International Journal of Engineering and Technology, 2018)
As the Very Large-Scale Integration (VLSI) techniques are mostly focused on high-speed and low power consumption circuits, various techniques and technologies were investigated to gain these two precious goals. Domino-logic is one of the circuits which is regarded to have high speed, high frequency and low power consumption. This work proposes a Domini logic circuit which has improved PDP compare to the previous one. The suggested circuit was simulated and the attained results show a considerable improvement in circuitâ€™s speed in respect with its ancestor. The PDP of the circuit in 90 nm, biased at 1V, has been calculated as 53% approximately improvement. This improvement for PDP in 65 nm, 45 nm and 32 nm are 48%, 47% and 51% respectively.Â Â